Intestinal microbiome-targeted therapies improve liver function in alcohol-related liver disease by restoring bifidobacteria: a systematic review and meta-analysis - Chi, Xin; Sun, Xiu; Cheng, Danying; Liu, Shunai; Q. Pan, Calvin; Xing, Huichun (Frontiers in Pharmacology, 2024)
Objective. To systematically evaluate the efficacy of intestinal microbiome-targeted therapies (MTTs) in alcohol-related liver disease (ALD).. With pre-specified keywords and strategies, we searched databases including Cochrane Library, PubMed, EMBASE, CNKI, Wanfang Data, and Weipu for RCTs on intestinal MTTs in ALD patients from Jan 2000 to May 2021. Two researchers independently conducted literature screening, data extraction, and quality evaluation according to the eligible criteria. Outcomes of interest included the effects of intestinal MTTs on ALT, AST, GGT, TBIL, TNF-α, IL-6, intestinal Escherichia coli, and Bifidobacteria when compared to the control group. Pooled data were compiled and analyzed with Revman 5.4 software.Results. Among 5 RCTs included with 456 ALD patients who received probiotics, the therapeutic pooled effects in the experimental group were the followings: ALT (MD=-7.16，95％ CI：-10.71~-3.60; P＜0.0001)、AST(MD=-25.11，95％ CI： -30.57~-19.47; P＜0.00001)、GGT(MD=-6.72，95％ CI：-11.91~-1.53; P=0.01) 、 IL-6(SMD=-0.82，95％ CI：-1.10~-0.54; P＜0.00001), which were significantly better than those in the placebo or standard treatment group respectively, while the difference of TBIL (SMD=-0.06, 95%CI: -0.29~0.16; P=0.59), TNF-α(SMD=-0.53， 95％ CI：-1.57~0.50; P=0.31)in the two groups was not significant. After intestinal MTT treatment, the number of intestinal Bifidobacteria increased significantly (MD=0.79，95％ CI：-0.00~1.58; P=0.05)in the experimental group. However, there were no significant changes in the number of E. coli in both groups (SMD=-0.29， 95％ CI：-0.92~0.34; P=0.36).Intestinal MTTs can significantly improve liver function, associated with the increase of intestinal Bifidobacteria, which may be beneficial to ALD.